Pengaruh Model Pembelajaran Kooperatif tipe Think Talk Write (TTW) Terhadap Prestasi Belajar Matematika Siswa Kelas VIII SMP - Nunung Supita Elisa; Nurul Hikmah; Muhammad Turmuzi; Arjudin Arjudin (Pendidikan Matematika FKIP Universitas Mataram, 2021)
This research aims to determine whether or not there is an effect of the TTW cooperative learning model on the mathematics learning achievement of class VIII students of SMPN 2 Batukiang Utara in the 2020/2021 academic year. This type of research is a quasi experiment with the posttest only control design with nonequivalent groups. The subjects in this study were class VIII A as the experimental class using the TTW learning model and VIII B as the Kontron class with the direct learning model. The data collection technique used a research instrument in the form of a description test. The statistical analysis used in this study is the t test and the effect size test. Based on the data analysis, the results of the posttest showed that the experimental class average was 62.28 and the control class was 51.25. This indicates that learning with the TTW cooperative model is better than direct learning. Data analysis with t-test at a significant level of 5% , namely 4.03≥1.67, and the effect size test with d = 1.17 (high). So it can be concluded that the type of cooperative learning model (TTW) affects the mathematics learning achievement of class VIII students of SMPN 2 Batukliang Utara in the 2020/2021 school year